Detailed investigation of liquid distribution and holdup in periodic open cellular structures using computed tomography - Littwin, Giulia; von Beyer, Markus; Freund, Hannsjörg (Chemical Engineering and Processing, 2021)
Periodic open cellular structures (POCS) show great potential for process intensification in catalytic reactors due to their favorable properties regarding heat transfer, pressure drop and liquid distribution. In multiphase applications, POCS can be employed as multifunctional catalyst carrier with integrated liquid distribution function for enhancing the performance of heterogeneously catalyzed reactions. This applies particularly to trickle bed reactors where a uniform liquid distribution is of great importance. In this contribution, the liquid distribution of three POCS of different unit cell geometry is investigated using a custom-made computed tomography scanner with high spatial resolution. POCS with the Kelvin, diamond and DiaKel unit cell, respectively, were manufactured via fused deposition modeling out of acrylonitrile butadiene styrene. The liquid distribution was examined in dependence of the unit cell as well as for different liquid and gas flow rates. The three POCS show different behavior for the liquid distribution and holdup within the structures. POCS with Kelvin and DiaKel unit cell geometry show a higher liquid holdup as well as a more uniform liquid distribution compared to diamond unit cell POCS. Also, the liquid filling between the individual POCS that are stacked in the column is dependent on the unit cell.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Computed tomography; Liquid distribution; Liquid holdup; Multiphase system; POCS; Trickle bed reactor

Periodic open cellular structures (POCS) for intensification of multiphase reactors: Liquid holdup and two-phase pressure drop - Lämmermann, Markus; Horak, Giulia; Schwieger, Wilhelm; Freund, Hannsjörg (Chemical Engineering and Processing, 2018)
Structuring concepts for catalytic reactors provide promising options for process intensification on the process unit level [1,2] as they offer a better control on the occurring transport processes, e.g. on the fluid flow, species distribution, pressure drop and heat transfer. Process intensification aims at the realization of processes that are only limited by reaction kinetics, but not anymore on hydrodynamics [3]. For this reason, in multiphase reactors it is desirable to achieve good liquid distribution, advanced heat transport and low pressure drop, just to mention a few transport characteristics. In this regards, the use of periodic open cellular structures (POCS) is a recent and very promising structuring concept, as packings of these structures offer superior and adjustable properties (e.g. low pressure drop, high surface area, good liquid distribution, advanced heat transfer) [4-8].In this contribution, static and dynamic liquid holdup as well as single- and two-phase pressure drop was measured in POCS. These kinds of structures can be used as catalyst support in packed bed reactors, and also as liquid distributor for trickle-bed applications. The POCS investigated in this study were fabricated with different additive manufacturing methods (fused deposition modeling, stereolithography and selective electron beam melting) to study the influence of different materials (ABS, resin, Ti6Al/4V). For the description of the static liquid holdup, a modified Eotvos correlation, which takes the contact angle of the different materials into account, is proposed. Dynamic liquid holdup and two-phase pressure drop was modelled using an extension of the concept of hydrodynamic tortuosity proposed by Inayat et al. [8], and a modification of the relative permeability model introduced by Saez et al. [9]. Furthermore, equations for the geometric characterization of POCS consisting of different unit cell types, namely Diamond, Kelvin and the recently presented DiaKel hybrid cell [5] were derived. The window diameter of the used unit cells as well as the porosity has a strong influence on the liquid holdup and the pressure drop. By taking the contact angle into account the static liquid holdup can be calculated with good precision (errors smaller than 20%). The concept of geometric tortuosity and the relative permeability model also is applicable to predict the (two-) phase pressure drop and the dynamic liquid holdup in stacked packings of POCS segments of different unit cells and materials. Both, pressure drop and liquid holdup can be predicted a priori (i.e., without further fitting) with good precision using the correlations established in this work solely based on geometric properties of the packing.
Keywords: Two-phase pressure drop; Liquid holdup; Structured catalysts; Relative permeability model; Additive manufacturing

Systematic Experimental Investigations and Modeling of the Heat Transfer in Additively Manufactured Periodic Open Cellular Structures with Diamond Unit Cell - Littwin, Giulia; Röder, Susanne; Freund, Hannsjörg (Industrial & Engineering Chemistry Research, 2021)
Additively manufactured periodic open cellular structures (POCS) represent a new class of structured catalyst carriers due to their favorable characteristics such as high specific surface area, low pressure drop, and remarkable heat transport properties. The periodic, well-defined, and reproducible geometry makes systematic investigations and geometric optimization possible. For a detailed optimization, models for the description of the transport characteristics of POCS are necessary. Besides the geometric parameters of the unit cell, the unit-cell geometry itself has a major effect on the dispersive thermal conductivity. POCS based on the diamond unit cell show a superior dynamic thermal conductivity in comparison to cubic structures and are therefore examined in detail. From the measurement results and the corresponding model parameters, influences of the geometric parameters of the structures are found. This leads to new design correlations for the heat transport in POCS. With this, a model-based optimization of POCS for a specific application, such as strongly exothermic reactions, is possible.
CRIS-Team Scopus Importer:2021-05-14